Exposure to PM2.5 and PM10 pollution and the risk of respiratory diseases in upper Silesia inhabitants - Kobza, Joanna; Grajek, Mateusz; Geremek, Mariusz; Działach, Eliza; Szlachta, Grzegorz (Journal of Education, Health and Sport, 2023)
Background: Multiple studies confirm that PM2.5 and PM10 can affect lung growth and development in children and adolescents, the number of medical visits, and hospital emergency admissions due to asthma, respiratory symptoms, and upper and lower respiratory tract disorders. Objective: The objective of this study was the measurement-based assessment for determining whether the concentrations of PM10 and PM2.5 are within admissible limits or exceeded in the Upper Silesia urban area (Silesia province) and to examine the relationship between PM concentrations and the number of admissions in Primary Health Care due to respiratory diseases like asthma and chronic bronchitis for children, adolescents and adults. Material and methods: The data provided by the Voivodship Inspectorate for Environmental Protection in Katowice, National Health Fund - Silesian Department, and the District Sanitary-Epidemiological Station in Katowice for the period 2012-2017 was used in the statistical analysis. Results: The increase in the number of excessive levels of average daily PM10 concentration was observed in almost all measurement stations, both for the acceptable level, information, and alarm level. The increase in average annual PM2.5 concentrations was also observed. The results showed an increased prevalence of respiratory diseases (ICD-Diagnosis Code 10-CM: J017, J030, J034, J038, J040) during the study period in 14 of 20 cities of Silesia province, consistently higher for children than adults. Conclusions: In Silesia province, the air quality is poor and has deteriorated over the last few years. Exposure to ambient PM2.5 and PM10 was significantly associated with the development of respiratory tract diseases in children and adults.